DIGITALIZATION AND ECONOMIC MODERNIZATION OF TRANSPORT SERVICES: INTERNATIONAL EXPERIENCE AND POLICY IMPLICATIONS FOR UZBEKISTAN - Sulaymonov Ibratjon Alisher ugli (Modern American Journals, 2025)
This study investigates the impact of transport system digitalization on economic growth in Central Asian countries using panel data analysis covering the period 2010–2020. Amidst regional challenges such as complex transport documentation, limited infrastructure, and high trade costs, digital transformation emerges as a strategic necessity. The research employs a panel regression model to evaluate how three key variables—railway infrastructure, trade volume, and online transport documentation platforms—affect GDP growth. Findings reveal that the digitalization of transport, particularly the implementation of electronic documentation systems, has a statistically significant and positive influence on economic growth, contributing up to 11% to GDP across the region. The study underscores the need for harmonized digital strategies and sustained investment in transport ICT infrastructure to unlock the region's economic potential and enhance connectivity. These results offer empirical evidence for policymakers to prioritize digital solutions in the transportation sector as a catalyst for sustainable economic development.
Keywords: Transport digitalization, economic growth, panel data analysis, Central Asia, online documentation systems, transport infrastructure